(untitled) (The Pakistan Development Review, 2012)
As an outcome of demographic transition the composition of the world’s population has changed. In turn percent share of population above 60 years of age will be doubled from 11 percent in 2010 to 22 percent in 2050 worldwide [United Nations (2011)]. Those countries which encountered demographic transition early are now facing the problem of ageing societies. In developing countries, demographic transition started late, and they have not yet encountered the problem of a large proportion of elderly in the population. However, in the coming years with the high proportion of elderly, these countries will also have to face the problems with their poor economic situation and burden of diseases. Therefore it will be a difficult task for developing countries to combat the problem of the large proportion of elderly in the population in the coming years if concrete steps have not been taken at this time. Pakistan, where demographic transition started in the 90’s, has almost six percent (more than nine million) of the population above 60 years of age in the year 2005, and it will rise to 16.5 percent (48 million) in the year 2050. If we look at the ageing index, which is the number of persons 60 years of age or above per hundred persons below 15 years of age, the value was 15.9 in 2005. It will rise to 29 in 2025 and further to 75.5 in the year 2050 due to decline in fertility and steady increase in life expectancy. The old-age dependency ratio has also increased from seven in 2005 to nine in 2025 and will reach 16 in the year 2050 [UN (2006)].